Hepatic encephalopathy - Wissam Bleibel; Abdullah M. S. Al-Osaimi (The Saudi Journal of Gastroenterology, 2012)
Chronic liver disease and cirrhosis affect hundreds of millions of patients all over the world. The majority of patients with cirrhosis will eventually develop complications related to portal hypertension. One of these recurrent and difficult to treat complications is hepatic encephalopathy. Studies have indicated that overt hepatic encephalopathy affects 30 to 45% of patients with cirrhosis and a higher percentage may be affected by minimal degree of encephalopathy. All of these factors add to the impact of hepatic encephalopathy on the healthcare system and presents a major challenge to the gastroenterologist, hospitalist and primary care physician.